Hematopoietic Stem Cell Transplantation in PML-RARa Positive Acute Promyelocytic Leukemia - Kamran Alimoghaddam; Ardeshir Ghavamzadeh; Mohamad Jahani; Arash Jalali; Hoda Jorjani; Massoud Iravani; Amir Ali Hamidieh; Asadolah Mousavi; Babak Bahar; Maryam Behfar; Roshanak Derakhshandeh; Shahrbanoo Rostami (International Journal of Hematology-Oncology and Stem Cell Research, 2011)
Introduction: Acute promyelocytic leukemia treatment revolutionized by new tretaMNETS. Currently number of patinets who undergoe hematopoietic stem cell transplantation decrased so experience with this modality is limited. Here we report our experience with stem cell transplantation in acute promyelocytic leukemia patients. Design and setting: retrospective, single center Methods: between year 2000 and 2011 we performed 20 HSCT in APL. Median age of patients was 25 year old. Patients received 3 autologous and 17 allogeneic HSCT from their HLA full match sibling donor. Different type of conditioning regimens applied for them. We used Cyclosporine and Methotraxtae as prophylaxis of GVHD after allogeneic HSCT. Results: Hematopoietic stem cell engraftment observed in all cases. Acute GVHD was mild to moderate in all except one and was manageable.one patient dies due to aGVHD. Chronic GVHD was extensive in 2 cases and one mortality observed due to sever cGVHD. Mortality rate was 35% with a median follow up of 3.5 years. Five patinets died due to their primary disease relapse after HSCT. Three years DFS and OS were 63.1 and 77.2% respectively. Conclusion: hematopoietic stem cell transplantation is an acceptable consolidation for APL. Choosing between autologous or allogeneic transplantation, need facilities such as reliable method for molecular remission detection before HSCT and also close and reliable follow up of patients with clinical and molecular parameters.